INVESTIGATION OF THE RELATIONSHIP BETWEEN SPIRITUAL WELL-BEING AND QUALITY OF LIFE IN BREAST CANCER PATIENTS - ADAM, MUHSINA TSOHO (Fırat Üniveristesi, 2022)
Bu çalışmanın amacı meme kanseri hastalarında yaşam kalitesi ve manevi iyi oluş arasındaki ilişkiyi incelemektir. Kesitsel tipteki bu çalışma Fırat Üniversitesi hastanesinde tedavi gören 91 meme kanseri hastası ile yürütülmüştür. Anket formunun ilk bölümünde kişisel bilgiler formu kullanılmıştır. İkinci bölümünde; Avrupa Kanser Tedavi ve Organizasyon Komitesi Yaşam Kalitesi Ölçeği (EORTC QLQ-C30) yaşam kalitesini, Manevi İyilik Hali Ölçeği (FACIT-Sp12) ise meme kanseri hastalarının manevi iyi oluşlarını değerlendirmek için kullanılmıştır. Katılımcıların genel yaşam kalitesi puanı 44.76±18.96; alt boyutlar arasında en yüksek puanı rol fonksiyonuna 60.32±8.87, en düşük puan ise duygusal fonksiyona 25.73±23.46 aittir. Semptom alt boyutunda ise finansal etki en yüksek puanı alırken 71.54±23.65; diyare en düşük puana 21.61±34.60 sahiptir. FACIT-Sp12 manevi iyi oluş ölçek puanı 24.79±4.80'dir. Semptom alt boyutu dışında yaşam kalitesinin her bir alt boyutu ile manevi iyi oluş ölçeklerinin alt boyutları arasında pozitif bir ilişki saptanmıştır (p<0.005). Semptom puanları azaldıkça yaşam kalitesi ve manevi iyi oluş puanları artmaktadır (p<0.001). Çalışmamızın sonucuna göre, meme kanseri hastaları yaşam kalitesi ve manevi iyi oluş düzeyleri kötü olarak saptanmıştır. Yaşam kalitesi ve manevi iyi oluş arasındaki ilişkiyi dikkate aldığımızda ise, meme kanseri olan kadınların daha fazla ruhsal ve manevi müdahalerle ihtiyaçları giderilmelidir.

This study aimed to investigate the relationship between spiritual well-being, and quality of life, for breast cancer patients. This cross-sectional study was conducted with 91 breast cancer patients treated at Fırat University Hospital. A personal information form was used in the first part of the questionnaire. In the second part; the European Cancer Treatment and Organizing Committee Quality of Life Scale (EORTC QLQ-C30) were used to measure the quality of life (QoL) and the Spiritual Well-Being Scale (FACIT-Sp12) was used to measure the spiritual well-being of the breast cancer patients. The result shows that the participants had an overall QoL score of 44.76 (SD=18.96), within the domains of EORTC QLQ-C30; in General health status, Role functioning has the highest score with a mean of 60.32 (SD =8.87) and emotional functioning has the lowest score with mean 25.73 (SD=23.46) while in symptoms, the financial impact has the highest mean score of 71.54 (SD=23.65); while diarrhea with a lowest mean score of 21.61 (SD=34.60). FACIT-Sp12 shows a total score of 24.79 (SD=4.80). There is a positive relationship between each domain of FACIT- Sp12 and the QLQ-C30 (p<0.005) except symptom subscale. The correlation coefficient showed a negative correlation between each of the subscales of FACIT- Sp12 and the QLQ-C30 (p<0.001). As symptoms decrease, quality of life and spiritual well-being increase. The results of our study showed that the level of quality of life and spiritual well-being of breast cancer patients were found to be poor. Considering the relationship between spirituality and quality of life, it is necessary to meet the needs of breast cancer with more psycho-spiritual interventions
Meme kanseri hastalarının manevi iyi oluşları ve yaşam kalitesi arasındaki ilişkinin incelenmesi
Keywords: Hemşirelik